Improving the HIV PrEP continuum of care using an intervention for healthcare providers: a stepped-wedge study protocol. Issue 7 (14th July 2020) - Ming, Kristin; Shrestha, Isha; Vazquez, Alexander; Wendelborn, James; Jimenez, Veronica; Lisha, Nadra; Neilands, Torsten B; Scott, Hyman; Liu, Albert; Steward, Wayne; Johnson, Mallory O; Saberi, Parya
Abstract : Introduction: Pre-exposure prophylaxis (PrEP) has demonstrated to be a highly effective method for preventing HIV; however, many individuals with PrEP indications are not receiving PrEP. Primary care settings provide an opportunity to offer PrEP to a wide range of patients. In this paper, we describe the PrEP Optimisation Intervention (PrEP-OI), which includes a PrEP Coordinator and a web-based panel management tool (called PrEP-Rx), and is targeted at healthcare providers (HCPs) to increase PrEP uptake and persistence among those at risk for acquiring HIV. Methods and analysis: The PrEP-OI study evaluates the efficacy of the PrEP intervention (PrEP Coordinator + PrEP-Rx) to increase PrEP prescriptions through a stepped-wedge design among 10 primary care clinical sites in the San Francisco Department of Public Health. The number of PrEP initiation prescriptions constitute the primary outcome, and we hypothesise that the mean number of PrEP prescriptions written will significantly increase after the clinics initiate PrEP-OI versus before this intervention. Secondary objectives include: 1-differences in PrEP initiation, duration of use and reasons for discontinuation based on patient's age, race/ethnicity and sex/gender, and by clinic and HCP characteristics, 2-sustainability of the intervention during a 12-month follow-up after the stepped-wedge phase, and 3-facilitators and barriers of PrEP delivery and experiences with the proposed PrEP intervention through qualitative interviews with HCPs. The results of this study can provide valuable insight into methods to reduce the burden of PrEP care on HCPs and improve PrEP continuum of care. Ethics and dissemination: This study and its protocols have been approved by the University of California, San Francisco (UCSF) Institutional Review Board. Study staff will disseminate findings locally (eg, the UCSF Centre for AIDS Prevention Studies' Community Engagement Core), statewide (eg, the California Department of Public Health's Office of AIDS) and nationally and internationally at conferences related to HIV. Trial registration number: NCT03532191 .